How life circumstances during public health crises affect people to share and correct misinformation: a perspective of the third-person effect - Tian, Xiang (Frontiers in Psychology, 2024)
Introduction Misinformation spreading on social media often parallels public crises, such as the outbreak of COVID-19, because people’s behaviors regarding misinformation may be influenced by their typical life circumstances. With the increasing severity of living conditions, misinformation is believed to spread more widely, while corrective behaviors tend to decrease. Furthermore, social comparison also affects the perception of life circumstances and subsequent behaviors. Taking Shanghai’s COVID-19 lockdown as an example, this study examined whether two representative factors—the duration of the lockdown and the satisfaction with relief measures—affected people’s tendency to share and correct misinformation. By employing the third-person effect (TPE) theory, the underlying mechanisms of social comparison were also explored. Methods An online survey was conducted in April 2022, when the Zero-COVID policy was implemented in Shanghai. In addition to questions about life circumstances, a third-person perception scale, a behaviors of sharing misinformation scale, and a behaviors of correcting misinformation scale were included in the survey. Finally, 7,962 valid responses were collected. Results It was found that both behaviors—sharing and correcting misinformation—were affected by life circumstances but in different ways. The evidence also supported the existence of third-person perception (TPP). It was observed that the relationship between satisfaction with relief measures and sharing behavior was mediated by Third-Person Perception. Conclusion This study reveals that the proliferation of misinformation during crises is related to the deterioration of people’s perception of life circumstances. Social comparison often plays a significant role, as was reflected by the TPE.